Kebijakan Pembelajaran Tatap Muka Sebagai Penggerak Usaha Mikro di Satuan Pendidikan - Muhamad Safiul Umam (EXERO : Journal of Research in Business and Economics, 2023)
The Large-Scale Social Restrictions Policy issued by the Covid-19 task force has a direct impact on the economic ecosystem in the education unit. The transportation sector and the buying and selling process have been completely halted for 20 months. Based on the formulation of the problem, the authors formulated the aim of capturing the scope of the movement of the Micro Business sector as a result of the Face-to-Face Learning policy in educational units. The research approach used is descriptive qualitative, the methods used are interviews, observation, and documentation with triangulation as a data validity technique. data analysis was carried out after data collection was declared complete to facilitate researchers in analyzing research data. Based on the results of the study, data on economic turnover were obtained from the attendance of students and GTK at SMAN 1 Pagai Utara Selatan after the PTM policy was implemented for the transportation service sector and school canteens for each type of business per year below 300,000,000.00. While the economic turnover for a combination of all types of businesses per year ranges from 786,000,000.00. It can be concluded based on the classification of MSMEs according to UU_No 20_Tahun 2008_about UMKM_Article 6, Micro Enterprises operate for each type of business thanks to the PTM policy at SMAN 1 Pagai Utara Selatan.